Sincerely held American secularism and its believers - McCrary, Charles 1990- (Chicago University of Chicago Press, 2022)
Intro -- Contents -- Introduction: The Character of American Secularism -- 1. Knaves, Fools, and Sincere Believers -- 2. Secular Governance in Columns and Rows -- 3. Telling Fortunes -- 4. "Religious Training and Belief" -- 5. Supreme Beings and the Supreme Court -- 6. Believing Religiously -- 7. Troubling Secularism -- 8. Sincerity Now -- Epilogue: On Being Sincere -- Acknowledgments -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Freedom Of Religion; Glaubensfreiheit; Laizität; Religionsfreiheit; Säkularismus; Electronic books; Usa